2017
DOI: 10.1002/jctb.5249
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous recovery of ammonium and phosphate from simulated treated wastewater effluents by activated calcium and magnesium zeolites

Abstract: BACKGROUND\ud \ud In this study a sodium zeolite synthesized from coal fly ash (NaP1-NA) was modified to calcium and magnesium forms (Ze-Ca, Ze-Mg) as sorbent materials for simultaneous recovery of ammonium and phosphate from simulated treated wastewater effluents.\ud RESULTS\ud \ud Increasing the temperature during the modification step to magnesium form improved the zeolite conversion. The maximum sorption capacities obtained were 123.1±9.1 mg NH4 g-1 and 119.5±7.5 mg PO4 g-1 in an ammonium/phosphate binary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…e synthesis of NaP1 from a hazardous Al-waste was performed by an eco-friendly bench-scale hydrothermal process [17], contributing to reduce the consumption of raw materials (i.e., water and NaOH) and environmental impact. Although both natural zeolites and zeolites from fly ash have been widely used to remove ammonium from waters [13,14,18,19], studies conduced for zeolites from highly Alenriched wastes have not been reported, to our knowledge, in the literature.…”
Section: Introductionmentioning
confidence: 85%
“…e synthesis of NaP1 from a hazardous Al-waste was performed by an eco-friendly bench-scale hydrothermal process [17], contributing to reduce the consumption of raw materials (i.e., water and NaOH) and environmental impact. Although both natural zeolites and zeolites from fly ash have been widely used to remove ammonium from waters [13,14,18,19], studies conduced for zeolites from highly Alenriched wastes have not been reported, to our knowledge, in the literature.…”
Section: Introductionmentioning
confidence: 85%
“…<1.0mg/L, Hg :<1.0×10 -3 mg/L, Mn: <0.05mg/L, and Zn:<5.0mg/L are regarded as non-toxic for the aesthetic objectives of drinking water. Na + and Mg 2+ as mentioned in the previous study [30]. For MNZ, it can be explained by the ion selectivity of NH4 + towards natural zeolites.…”
Section: Trace Elemental Analysis By Leaching Testsupporting
confidence: 58%
“…You et al [30] observed the IR spectrum NH4 + (1434 cm -1 ) and PO4 3-(997 cm -1 ) on spent Ze-Mg, which are also similar to IR spectrum of struvite. However, the presence of struvite was not confirmed neither by XRD nor SEM image.…”
Section: Determination Of the Amounts Of P On Spent Zeolite Samplesmentioning
confidence: 61%
See 2 more Smart Citations